Seismic Analysis of Concrete Folded Plates - Hammood, Aqeel M.; Jawad, David A. M. (Basrah Journal for Engineering Sciences, 2024)
Concrete roof-folded plates have been shown to be inherently resilient to earthquakes, despite limited research on the reasons for their apparent seismic resistance. It is possible to make very thin, folded concrete plates because of their high structural efficiency. It is implicitly resistant to earthquake forces because thin, folded plat structures are relatively lightweight. Typically, folded plate structures are designed to perform under ideal gravity loads that are transported primarily as a result of membrane activity across the surface. It is possible for concrete-folded plate structures to be damaged by bending stresses when earthquakes induce unexpected horizontal forces. Through a parametric analysis of an 8-cm-thick concrete roof folded plate structure, it has been shown that thin concrete roof folded plates with a span < 30 m can be intrinsically earthquake-resistant. Despite having a low mass and high geometric stiffness, these buildings have fundamental frequencies that are substantially higher than those connected to seismic events that actually occur. This characteristic causes the folded plate to behave elastically under earthquake excitation without exceeding the maximum concrete strength. The vertical components of earthquake vibrations exert greater stress on a shallow, folded plate than the horizontal components. The values of the stresses imposed by the changing span were relatively small. They ranged from (3.5-4.4) MPa for the Landers earthquake, while for the El Centro earthquake, they ranged from (2.7-8.6) MPa. In addition, by raising the folded big plates and inclining them to a greater angle, it will become more common and lessen the harm caused by earthquake shaking in the vertical direction. In general, this paper aims to present an examination of earthquakes and their consequences for folded concrete plates.